Angiotensin II‐induced renal angiotensinogen formation is enhanced in mice lacking tumor necrosis factor‐alpha type 1 receptor. Issue 16 (24th August 2021) - Majid, Dewan S. A.; Mahaffey, Eamonn; Castillo, Alexander; Prieto, Minolfa C.; Navar, L. Gabriel
Abstract: In hypertension induced by angiotensin II (AngII) administration with high salt (HS) intake, intrarenal angiotensinogen (AGT) and tumor necrosis factor‐alpha (TNF‐α) levels increase. However, TNF‐α has been shown to suppress AGT formation in cultured renal proximal tubular cells. We examined the hypothesis that elevated AngII levels during HS intake reduces TNF‐α receptor type 1 (TNFR1) activity in the kidneys, thus facilitating increased intrarenal AGT formation. The responses to HS diet (4% NaCl) with chronic infusion of AngII (25 ng/min) via implanted minipump for 4 weeks were assessed in wild‐type (WT) and knockout (KO) mice lacking TNFR1 or TNFR2 receptors. Blood pressure was measured by tail‐cuff plethysmography, and 24‐h urine samples were collected using metabolic cages prior to start (0 day) and at the end of 2nd and 4th week periods. The urinary excretion rate of AGT (uAGT; marker for intrarenal AGT) was measured using ELISA. HS +AngII treatment for 4 weeks increased mean arterial pressure (MAP) in all strains of mice. However, the increase in MAP in TNFR1KO (77 ± 2 to 115 ± 3 mmHg; n = 7) was significantly greater ( p < 0.01) than in WT (76 ± 1 to 102 ± 2 mmHg; n = 7) or in TNFR2KO (78 ± 2 to 99 ± 5 mmHg; n = 6). The increase in uAGT at 4th week was also greater ( p < 0.05) in TNFR1KO mice (6 ± 2 to 167 ± 75 ng/24 h) than that in WT (6 ± 3 to 46 ± 16 ng/24 h) or in TNFR2KO mice (8 ± 7 to 65 ± 44 ng/24 h). The results indicate that TNFR1 exerts a protective role by mitigating intrarenal AGT formation induced by elevated AngII and HS intake. Abstract : We examined the hypothesis that elevated AngII levels during HS intake reduce TNF‐α receptor type 1 (TNFR1) activity in the kidneys, thus facilitating increased intrarenal AGT formation. The responses to HS diet (4% NaCl) with chronic infusion of AngII (25 ng/min) via implanted minipump for 4 weeks were assessed in wild‐type (WT) and knockout (KO) mice lacking TNFR1 and TNFR2 receptors. HS +AngII treatment for 4 weeks increased mean blood pressure (MBP) in all strains of mice. However, the increase in MBP in TNFR1KO was greater than that in WT or in TNFR2KO. The increase in urinary angiotensinogen excretion (UAGT) at the 4th week was also greater in TNFR1KO mice than that in WT or in TNFR2KO mice. The results indicate that TNFR1 activity exerts a protective role by mitigating intrarenal AGT formation induced by elevated AngII and HS intake.